A qualitative study on the experiences of the prospective brides about nutritional preparation during the preconception period - Emirza, Phellia; Wiradnyani, Luh Ade Ari; Ermayani, Evi (Indonesian Nutrition Association, 2025)
Background: Stunting is still a nutritional problem in Indonesia, where maternal malnutrition is one of the causes. Studies show that prospective brides and women of childbearing age in Indonesia are not physically and knowledgeably ready for pregnancy. Nutritional preparation is crucial during preconception, as preconception nutritional status can have cross-generational impacts, yet it is often overlooked. Objective: This study aimed to explore the experiences of prospective brides regarding nutritional preparation during the preconception period. Methods: This qualitative research was conducted in Bogor, Indonesia, using in-depth interviews and participatory methods. The main informants of this study were 20 prospective brides selected through convenience sampling. Additionally, 21 key informants were involved for triangulation. Data analysis was conducted by coding verbatim transcripts using NVivo12 software. The results of this study used a pre-determined theme aligned with the research objectives. Result: Almost all informants agreed that preconception nutritional preparation was crucial before marriage. Several nutritional preparation activities carried out by prospective brides emerged from this study, such as pre-pregnancy weight management and eating nutritious and healthier foods. However, many prospective brides still did not perform these activities optimally. Conclusion: Many prospective brides were already putting efforts to undertake nutritional preparation. However, knowledge gaps and misunderstandings among brides and grooms regarding nutritional preparation persist. There is a need to improve their awareness at preconception period and ensure government programs are accessible, equitable, and effective. This study offers new insights into nutritional preparation for brides, an area that is underexplored.